Acute Invasive Rhino-Orbital Mucormycosis in a Patient With COVID-19-Associated Acute Respiratory Distress Syndrome - Mekonnen, Zesemayat K; Ashraf, Davin C; Jankowski, Tyler; Grob, Seanna R; Vagefi, M Reza; Kersten, Robert C; Simko, Jeffry P; Winn, Bryan J (Ophthalmic plastic and reconstructive surgery, 2021)
Acute invasive fungal rhinosinusitis is a rare, although highly morbid, infection primarily affecting immunosuppressed individuals. The same population is at particularly high risk of complications and mortality in the setting of SARS-CoV-2 infection and coronavirus disease 2019 (COVID-19)-related acute respiratory distress syndrome. The authors present a case of acute invasive fungal rhino-orbital mucormycosis in a patient with COVID-19 and discuss the prevalence, diagnosis, and treatment of fungal coinfections in COVID-19. Prompt recognition, initiation of therapy, and consideration of the challenges of rapidly evolving COVID-19 therapy guidelines are important for improving patient survival.